Pengaruh Content Marketing pada Instagram terhadap Customer Engagement dan Brand Awareness Miniso Indonesia - Fauzi, Syakirah Humaira; Sarasati, Fajar (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
This study is motivated by the low level of audience interaction with the Instagram content of @minisoindo, despite the account having a large number of followers. This shows that there are challenges in utilizing social media optimally to increase customer engagement and build brand awareness. The purpose of this study is to analyze the influence of content marketing on customer engagement and brand awareness, as well as identify the most effective content strategy elements in supporting these two variables. This study uses a quantitative approach with an explanatory method. Data was collected through an online survey of 100 respondents who were followers of the @minisoindo Instagram account using a non-probability sampling technique with a purposive sampling approach. Data analysis was carried out with SEM-PLS. The findings show that content marketing has a positive and significant effect on customer engagement by 77,9% and on brand awareness by 57,3%. In addition, the study found that easy-to-understand, easy-to-find, and accurate content is the most effective element of strategies in building customer engagement and strengthening brand awareness. Future research is recommended to examine the effectiveness of content marketing on other platforms such as TikTok, YouTube, or X by employing a mixed methods approach to gain deeper insights.